2018
DOI: 10.1007/s11046-018-0283-4
|View full text |Cite
|
Sign up to set email alerts
|

Putting It All Together to Understand the Role of Malassezia spp. in Dandruff Etiology

Abstract: Dandruff is a common scalp condition causing both a discomfort and an undesired social image. Various studies dating from early 1900s have investigated the condition, but understanding of underlying mechanisms and etiology of the condition is still in its infancy. Formation of dandruff is a common but complex event which has been associated with numerous causal factors. Physiological conditions such as pH, water content, or sebum secretion are some of the host-related factors. An imbalance between these factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
0
10
0
5
Order By: Relevance
“…Recently, associations between scalp SD and scalp microbiome such as bacterial commensals and presence specific strains of Malassezia yeasts have been published. This information helps fill the gaps in the pathophysiology of scalp SD which is still not completely understood [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, associations between scalp SD and scalp microbiome such as bacterial commensals and presence specific strains of Malassezia yeasts have been published. This information helps fill the gaps in the pathophysiology of scalp SD which is still not completely understood [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…M. restricta and M. globosa are the predominated species in human scalp Malassezia colonization. In particular, M. restricta has a critical role in the pathogenesis of dandruff and SD among the different species of Malassezia [ 32 35 ]. Recent studies from French, Indian, Chinese, and Korean populations demonstrated that M. restricta is more abundant in scalps with dandruff disease than in healthy scalps [ 8 , 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…is dependent on lipids (except for M. pachydermatis ), they are mainly distributed in areas rich in sebum, such as the scalp, where they account for 50–80% of the total number of colonizing fungi in healthy people. 35 Most of the symptoms in the population with sensitive scalps were scalp itching and Malassezia spp. colonization of the scalp showed a positive correlation with itching.…”
Section: Discussionmentioning
confidence: 99%